Rethinking science education : philosophical perspectives - Schulz, Roland M. (Science and engineering education sources., 2014)
This book presents a "philosophy of science education" as a research field as well as its value for curriculum, instruction and teacher pedagogy. It seeks to re-think science education as an educational endeavour by examining why past reform efforts have been only partially successful, including why the fundamental goal of achieving scientific literacy after several "reform waves" has proven to be so elusive. The identity of such a philosophy is first defined in relation to the fields of philosophy, philosophy of science, and philosophy of education. It argues that educational theory can support teacher's pedagogical content knowledge and that history, philosophy and sociology of science should inform and influence pedagogy. Some case studies are provided which examine the nature of science and the nature of language to illustrate why and how a philosophy of science education contributes to science education reform. It seeks to contribute in general to the improvement of curriculum design and science teacher education. The perspective to be taken on board is that to teach science is to have a philosophical frame of mind--about the subject, about education, about one's personal teacher identity.